Toxicological Evaluation of Anti-Scrapie Trimethoxychalcones and Oxadiazoles - Claudia P. Figueiredo (Anais da Academia Brasileira de Ciências, 2015)
An altered form of the cellular prion protein, the PrPSc or PrPRes, is implicated in the occurrence of the still untreatable transmissible spongiform encephalopathies. We have previously synthesized and characterized aromatic compounds that inhibit protease-resistant prion protein (PrPRes) accumulation in scrapie-infected cells. These compounds belong to different chemical classes, including acylhydrazones, chalcones and oxadiazoles. Some of the active compounds were non-toxic to neuroblastoma cells in culture and seem to possess drugable properties, since they are in agreement with the Lipinski´s rule of 5 and present desirable pharmacokinetic profiles as predicted in silico. Before the evaluation of the in vivo efficacy of the aromatic compounds in scrapie-infected mice, safety assessment in healthy mice is needed. Here we used Swiss mice to evaluate the acute toxicity profile of the six most promising anti-prionic compounds, the 2,4,5-trimethoxychalcones (J1, J8, J20 and J35) and the 1,3,4-oxadiazoles (Y13 and Y17). One single oral administration (300 mg/kg) of J1, J8, J20, J35, Y13 and Y17 or repeated intraperitoneal administration (10 mg/kg, 3 times a week, for 4 weeks) of J1, J8 and J35, did not elicit toxicity in mice. We strongly believe that the investigated trimethoxychalcones and oxadiazoles are interesting compounds to be further analyzed in vivo against prion diseases.